Unequally Spaced Channels Wavelength Division Multiplexing System - Yasser, Hassan (University of Thi-Qar Journal of Science, 2008)
The channels contributed in creating new pulse during the four-wavemixing (FWM) process are a subject of two features: the first is the fact thatall channels are not working with probability %100 , but with p probability. Second, the bits transmitted are not all "1". Therefore, the equation of power generated using these features should be corrected. Onthe other hand, the use of equally spaced channels wavelength divisionmultiplexing(ESCWDM)systemcauseanincreaseinthenumberofnewcomponentsgenerated that interfere with the active channels and increase the bit error rate. In order to reduce these interferences, we have providedan unequally spaced channels wavelength division-multiplexing (USC WDM) system composed of several sets. Each set consists of only fourchannels, which locations have been selected to cause no interferences between them. Neighboring sets are separated by a frequency spacing whichshould be large enough to reduce the interferences between the sets, andsmall enough to increase the total number of channels of the system.